Microfinance and Poverty Reduction in Nigeria: An Empirical Assessment Using Secondary Data from 2005–2023 - Sani Inusa Milala; Ja’afar Garba Ya’u Gwarmai (Jurnal Restorasi : Hukum dan Politik, 2025)
The Nigerian real estate sector has emerged as a critical component of the capital market, yet its performance has been undermined by persistent macroeconomic instability, inflationary pressures, and structural constraints such as poverty and unemployment. Despite its potential to drive economic growth and wealth creation, limited empirical studies have comprehensively examined the dynamics of real estate investment performance using secondary data across a long timeframe. This gap underscores the need for a systematic investigation of how macroeconomic variables and capital market indicators shape real estate investment outcomes in Nigeria. The aim of this study is to evaluate the performance of real estate investment within the Nigerian capital market from 2005 to 2023, focusing on the interplay between investment indicators, macroeconomic conditions, and social outcomes. A quantitative research design was employed, relying exclusively on secondary data sourced from the Central Bank of Nigeria (CBN), the National Bureau of Statistics (NBS), the World Bank, and other reputable online repositories. Descriptive statistics were used to summarize the trends, while correlation and regression analyses were applied to establish relationships among variables and test the study hypotheses. The descriptive results showed that real estate investment returns averaged 9.83 percent (SD = 3.01), with market capitalization averaging NGN 746.7 billion (SD = 272.09), highlighting growth potential despite volatility. Poverty headcount remained high, averaging 35.35 percent, while inflation (M = 11.15, SD = 2.41) and unemployment (M = 6.55, SD = 1.35) persisted as structural challenges. The correlation matrix revealed strong positive relationships between market capitalization and the real estate index (r = 0.956), as well as between the stock index and real estate index (r = 0.901). Regression analysis confirmed that market capitalization (β = 0.48, p < 0.01) and stock index (β = 0.36, p < 0.05) significantly predict real estate performance, whereas interest rates had weak and insignificant effects (β = 0.07, p > 0.10). The study concludes that real estate investment performance in Nigeria is primarily shaped by capital market growth and inflationary trends, while interest rates exert minimal direct influence. Strengthening capital market integration, stabilizing inflation, and linking financial inclusion policies to housing finance are recommended to enhance the sector’s sustainability and its role in poverty reduction.